Effect of Maximal Aerobic and Anaerobic Exercise on Blood Zinc and Copper Levels of Male Athletes - SAVAS, SEYFI (Asian Journal of Chemistry, 2010)
This study was carried out with 48 healthy male participants. They were separated into 3 equal groups with average age, body weight and heights as follows: Group 1 (aerobic group) with 22.69 ± 1.92 years, 80.69 ± 2.89 kg and 181.50 ± 4.00 cm; Group 2 (anaerobic group) with 21.56 ± 1.90 years, 80.94 ± 3.30 kg and 181.69 ± 2.50 cm and Group 3 (control group): 22.0 ± 1.32 years, 79.19 ± 3.41 kg and 181.63 ± 2.87 cm. The differences in blood zinc levels before and after aerobic and anaerobic loading (1 and 2 groups) were found to be statistically significant (p < 0.01). The post maximal aerobic exercise blood copper levels showed a statistically decrease compared to pre exercise levels (p < 0.01). This difference was found to be statistically insignificant for the anaerobic group (group 2) (p > 0.01). The difference between the pre and post test values of the control group also showed no statistically significant change as regards to both metals (group 3) (p > 0.01). In conclusion, it could be stated that aerobic exercises have more effects on reducing the blood zinc and copper level of athletes.